Development and validation of the Self-efficacy, Knowledge, Attitude and Practice towards Environmental Tobacco Smoke (SE-KAP-ETSQ) in the Malay language for mothers with children below 6 years old. - Ariffin, Farnaza; Ahmad-Roslan, Ahmad Muslim; Isa, Mohamad Rodi; Shanmunagathan, Punithavathy (IIUM Medical Journal Malaysia, 2022)
Introduction: Children under 6-years old are most susceptible to environmental tobacco smoke (ETS). Mothers spend more time with their children and need to be empowered to protect their children from ETS. The study aimed to develop and validate a Malay ETS questionnaire that measures the self-efficacy, knowledge, attitude, and avoidance practice (SE-KAP-ETSQ) among mothers with children below 6 years old. Materials and Methods: The SE-KAP-ETSQ was adapted from two questionnaires; 10-item EEQ and 29-item KAP-ETSQ. The two phases of the study are phase 1: development of the questionnaire and phase 2: validation of the questionnaire. Data were analysed using SPSS ver.26 and AMOS ver.24. Result: A total of 513 mothers; Exploratory factor analysis (EFA) was 186 and Confirmatory factor analysis (CFA) was 327 responded with a mean age of 31.44 years. EFA identified four domains with 26 items. Factor loadings ranged from 0.574 to 0.854 and Cronbach’s alpha ranged from 0.755 to 0.887. CFA generated four models before it achieved best-fit indices with root mean square error of approximation (RMSEA) of 0.053, goodness-of-fit index (GFI) was 0.932, comparative fit index (CFI) was 0.968, Tucker-Lewis index (TLI) was 0.960, Chi-squared/degree of freedom (ꭓ2/df) was 1.909, that left 17 items with factor loadings ranged from 0.614 to 0.948. Composite reliability and average variance extracted of the domains ranged from 0.778 to 0.858 and 0.534 to 0.689, respectively. Conclusion: This study produced a valid and reliable new Malay SE-KAP-ETSQ that can be used for further studies within a wider population.